2019
DOI: 10.1016/j.molcel.2019.03.013
|View full text |Cite
|
Sign up to set email alerts
|

RRM Transcription Factors Interact with NLRs and Regulate Broad-Spectrum Blast Resistance in Rice

Abstract: Nucleotide-binding site leucine-rich repeat (NLR) receptors perceive pathogen effectors and trigger plant immunity. However, the mechanisms underlying NLR-triggered defense responses remain obscure. The recently discovered Pigm locus in rice encodes a cluster of NLRs, including PigmR, which confers broad-spectrum resistance to blast fungus. Here, we identify PIBP1 (PigmR-INTERACTING and BLAST RESISTANCE PROTEIN 1), an RRM (RNArecognition motif) protein that specifically interacts with PigmR and other similar N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 60 publications
0
79
0
Order By: Relevance
“…By contrast, the higher PigmS level in panicle suppresses PigmR‐activated immune responses, which favors reproductive growth and in agriculture could reduce the yield loss caused by strong immunity. This case highlights that regulation of paired antagonistic NLRs is a novel mechanism balancing plant immunity and development (Deng et al 2017; Zhai et al 2019). NLR clusters seem a common phenomenon in the plant genome, and several recent reviews have made detailed discussions on this topic (van Wersch and Li 2019).…”
Section: Recent Discoveries Of the Activation Of Intracellular Nlrsmentioning
confidence: 96%
“…By contrast, the higher PigmS level in panicle suppresses PigmR‐activated immune responses, which favors reproductive growth and in agriculture could reduce the yield loss caused by strong immunity. This case highlights that regulation of paired antagonistic NLRs is a novel mechanism balancing plant immunity and development (Deng et al 2017; Zhai et al 2019). NLR clusters seem a common phenomenon in the plant genome, and several recent reviews have made detailed discussions on this topic (van Wersch and Li 2019).…”
Section: Recent Discoveries Of the Activation Of Intracellular Nlrsmentioning
confidence: 96%
“…Regarding BPA genes, 60 alternative splicing events that lead to the peptide change were identified from 24% (39 out of 161) plant members, with 23 events causing the disruption of RRM_1 domain. RRM domain containing protein has important roles in regulating plant defense (Zhai et al 2019), and domain-disrupted isoforms often exhibit remarkably different functions when compared with their corresponding normal proteins (Finet et al 2013). Therefore, the widespread occurrence of alternative splicing in plant BPAs may also increase their functional diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Motif 1 corresponds to RRM_1 (RNA recognition motif) domain. It was recently reported that the domain-containing gene may play a key role in plant immunity (Zhai et al 2019) while none of other motifs can be found in the Pfam database. They distribute unevenly in different clades and angiosperm groups with motif 10 being specific to fungi.…”
Section: Bpa Genes Exhibit Early Divergence In Angiospermsmentioning
confidence: 99%
“…A recent study suggested that the LRR domain of ZAR1 plays an important role in interaction with the decoy RKS1, while also helping to maintain ZAR1 in an autoinhibition state through intramolecular interactions (Wang et al , 2019a). Both the CC and TIR domains have been shown to function as signalling components in plant NLRs (Swiderski et al , 2009; Bernoux et al , 2011; Baudin et al , 2017; Wang et al , 2018; Zhai et al , 2019). Indeed, the CC or TIR domains of numerous NLR proteins can trigger cell death when transiently expressed in Nicotiana benthamiana (Bernoux et al , 2011; Bai et al , 2012; Wang et al , 2015; Cesari et al , 2016; Hamel et al , 2016; Baudin et al , 2017; Kim et al , 2018).…”
Section: Introductionmentioning
confidence: 99%